2014
DOI: 10.1097/qai.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Treatment, and Control of Dyslipidemia and Hypertension in 4278 HIV Outpatients

Abstract: Although most patients with HIV and LDL-C dyslipidemia or hypertension are treated, a significant percentage did not have adequate control of these risk factors. As patients with HIV are at higher risk for CVD and living to an age where CVD is more common, it will be important to identify ways to better manage and control CVD risk factors in this patient population. A comprehensive care model such as our setting may serve as an option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 18 publications
3
31
2
Order By: Relevance
“…Other authors described patients with HIV‐PAH as younger than other forms of PAH, and, unlike idiopathic PAH, which is more common in women than in men (ratio of men to women 1 : 1·7), in HIV‐PAH patients the men are more frequently affected by HIV‐PAH, possibly reflecting the high prevalence of men in HIV population .…”
Section: Pulmonary Hypertension In Hivmentioning
confidence: 98%
“…Other authors described patients with HIV‐PAH as younger than other forms of PAH, and, unlike idiopathic PAH, which is more common in women than in men (ratio of men to women 1 : 1·7), in HIV‐PAH patients the men are more frequently affected by HIV‐PAH, possibly reflecting the high prevalence of men in HIV population .…”
Section: Pulmonary Hypertension In Hivmentioning
confidence: 98%
“…Metabolic comorbidities among HIV‐infected persons have been examined in other large observational cohort studies including the EuroSIDA study , Data Collection on Adverse Events of Anti‐HIV Drugs (D:A:D) study , Swiss HIV Cohort Study , HIV Outpatient Study (HOPS) , Veterans Aging Cohort Study (VACS) and its Virtual Cohort (VACS‐VC) , Multicenter AIDS Cohort Study (MACS) , Women's Interagency HIV Study (WIHS) , North American AIDS Cohort Collaboration on Research and Design (NA‐ACCORD) , and an electronic medical record (EMR) study at a health care centre in New York City . Despite recent publications, however, robust prevalence estimates based on recent data are largely unavailable: data collection for the aforementioned studies occurred mostly prior to 2010, metabolic variables were often reported as baseline covariates in longitudinal analyses or in smaller substudies focused on other health outcomes, and restrictive analytic inclusion/exclusion criteria have sometimes resulted in study samples that were not representative of the larger population of HIV‐infected patients (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is common among HIV+ individuals with prevalence estimates from recent studies ranging from 19 to 52 % [33][34][35][36][37][38][39]. Some, but not all, studies have found the prevalence of hypertension to be higher among HIV+ compared with HIV− individuals.…”
Section: Hypertension In Hiv+ Individualsmentioning
confidence: 93%